Decision Support System Of Micro Business Credit Using The SAW Method At Bank Mandiri Pematangsiantar Sudirman Branch Based On Web-Based - Muhammad Alpin Alpin (Sean Institute, 2021)
Bank Mandiri Pematangsiantar Sudirman branch is a banking financial institution that accepts deposits, savings, or other forms and distributes funds as a business. At Bank Mandiri Pematangsiantar, there is always a graduation requirement for prospective debtors to be able to apply for credit/loans. Prospective debtors must meet the requirements to meet the criteria for applying for microcredit at the Sudirman branch of Bank Mandiri Pematangsiantar. And to determine prospective debtors who are entitled to receive credit, bank employees must determine several criteria that must be met by prospective debtors. This problem can be solved by the simple additive weighting (SAW) method in determining criteria and making decisions. This method will provide an alternative weighting with the largest weight being the choice that will be determined as a new prospective customer at Bank Mandiri Pematangsiantar